Factors Affecting the Marketing Efficiency of Gambier Commodity in Lima Puluh Kota Regency, West Sumatra, Indonesia - Muhammad Hendri; Rahmat Syahni; Nofialdi Nofialdi; Ifdal Ifdal (Universitas Andalas, 2020)
This research is motivated by the condition of Gambier marketing in Limapuluh Kota Regency, the Gambier center of West Sumatera and Indonesia, which is still experiencing problems and tends to be inefficient because of the high marketing margins, and the low share received by farmers. This study aims to analyze what factors influence the marketing efficiency of Gambier commodities in Lima Puluh Kota Regency. In this study, the researcher uses a Structural Equation Model (SEM) PLS method by taking 100 Gambier producers from Kapur IX sub-district and Pangkalan Koto Baru sub-district as research sites. The results showed that the variables of human resources, marketing institutions, products, capital, and markets significantly affect the marketing efficiency of Gambier commodities in the research site. Only the variable of government policy did not have a substantial impact on marketing efficiency